Validación de un cuestionario para evaluar valores personales y sociales en jóvenes deportistas (2019)
The purpose of this manuscript is to describe the construction and validation of a measurement instrument whose functionality is to learn about young athletes' behaviors in social and personal matters, and to demonstrate the influence of education of values through sports practices. The population chosen for the pilot study consisted of 40 children belonging to distinctive sports clubs, which were part of different football training schools in the city of Ibague (Colombia). The validation was achieved after processing the concepts issued by each of the experts whom the instrument was submitted to for evaluation, and after estimating its internal consistency by using Cronbach Alpha analysis. Our results establish that the questionnaire is valid and reliable to determine personal and social values in the community studied. © Copyright: Federación Española de Asociaciones de Docentes de Educación Física (FEADEF)